Experimental and numerical analysis on the structural behaviour of cold-formed steel beams subjected to fire - Laím, Luís (2013)
Tese de Doutoramento em Engenharia de Segurança ao Incêndio, apresentada à Faculdade de Ciências e Tecnologia da Universidade de Coimbra